Sejarah Perjuangan Pendiri Masjid Baiturrokhmah Cimahi dalam Penyebaran Ajaran Islam Abad ke-20 M - Febri Nugraha; Tarpin Tarpin (UIN Sunan Gunung Djati Bandung, 2023)
This study was conducted to examine the history of the struggle of the founder of the Baiturrokhmah Cimahi Mosque in the spread of Islamic teachings in the 20th century AD. Islamic Teachings and Their Orders. In the process of collecting sources, the author conducted interviews about the Biography of the Founder of the Baiturrokhmah Mosque (KH. Usman Dhomiri), the History of the Establishment of the Baiturrokhmah Cimahi Mosque, and the Struggle to Spread Islamic Teachings and Their Orders, with the great-grandson of K.H. Usman Dhomiri. In addition, the author also conducted an online search, which was collected in the form of ebooks, journals, theses, and credible websites. This study uses the Historical Method, which is carried out through 4 stages, namely Heuristics, Criticism, Interpretation, and Historiography.. Based on the results of the study, it can be concluded that K.H. Usman Dhomiri played an important role in spreading and developing the teachings of Islam and its Tarekat in Cimahi, even to several other areas in West Java. K.H. Usman Dhomiri shows that his leadership benefits the community.